Monitoring of Blood Cholesterol Measurement System Using ICT-Based Non-Invasive Methods - Oktariadi, Nanda; Alaydrus, Mudrik (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Coronary heart disease is a public health problem because of its very high morbidity and mortality, the death rate caused by coronary heart disease is quite high in the world, including in Indonesia. This study aims to analyze and develop and realize the application of non-invasive blood cholesterol measurement based on ICT. Contribution of this research is that it can be used as a reference or recommendation for developing a non-invasive ICT-based blood cholesterol measurement system. The research method used in this study is the library study method and the experimental method. The results of this study are: (1) The monitoring system for measuring blood cholesterol levels Non-invasive methods using near infrared technology can be implemented properly and can be monitored based on ICT using webBase; (2) Tests were carried out on 25 random samples with two conditions, conditions before eating and conditions after eating and compared with the invasive method (auto check), found an accuracy value in conditions before eating of 98.47% with an error value of 1.53%, while in the condition after eating found an accuracy of 98.55% with an error value of 1.45%; (3) Testing the blood cholesterol level detection tool with Non-invasive shows a more real time with a duration of 10 seconds until the results are displayed on the LCD screen, while with an invasive method it shows a measurement duration of 26 seconds until the results are displayed on the screen. (4) Based on this test, a non-invasive cholesterol level measuring device can be used as a reference in the development of a blood cholesterol measurement tool so that it can be an option for routine measurements.